Examining the effects of mixed and non‐digital gamification on students' learning performance, cognitive engagement and course satisfaction. (21st June 2022) - Qiao, Shen; Yeung, Susanna Siu‐sze; Zainuddin, Zamzami; Ng, Davy Tsz Kit; Chu, Samuel Kai Wah
Abstract: Gamification is typically implemented digitally. However, digital gamification is not always possible because of limited resources and logistical problems. It is thus necessary to explore low‐threshold gamification methods that can be easily adopted in classrooms. One such method is non‐digital gamification using physical game design elements. Currently, the literature provides a limited understanding of the design and effects of non‐digital gamification. It is also unclear whether mixed gamification (ie, a combination of digital and non‐digital gamification) is better than purely non‐digital gamification. We explored these topics using an explanatory sequential mixed‐methods design to compare the effectiveness of non‐digital gamification in a face‐to‐face course and mixed gamification in a blended course in terms of student learning achievement, cognitive engagement and course satisfaction. Two secondary grade classes were randomly assigned to the mixed ( N  = 52) or non‐digital ( N  = 52) gamification conditions. Contrary to our expectations, the quantitative results showed that the two approaches improved the students' learning achievement to the same extent. Although the students in the non‐digital gamification condition reported significantly higher‐course satisfaction than those in the mixed condition, the improvement in student cognitive engagement was significantly greater in the mixed gamification condition than in the non‐digital condition. Through focus group interviews, we analysed the students' learning experiences and synthesised the factors that influenced student cognitive engagement and course satisfaction. Practitioner notes What is already known about this topic Gamification is increasingly being used to increase student engagement and enhance learning. Gamification studies have mostly focused on digital modes, which often require gamified digital platforms or applications. Non‐digital gamification can be an effective method to foster learning, but the design and evaluation of non‐digital gamification is at an early stage. What this paper adds We designed non‐digital and mixed (ie, a combination of digital and non‐digital) gamification programmes and compared their effects using an explanatory sequential mixed‐methods design. Both gamification approaches led to a similar improvement in learning achievement. While non‐digital gamification fostered students' course satisfaction, mixed gamification was more effective in improving students' cognitive engagement. Implications for practice and/or policy Non‐digital gamification can be an effective low‐threshold solution for instructors. It is worth further improving the non‐digital gamification approach in school settings as it is cost‐effective and can be transferred between classrooms. The benefits of mixed gamification should not be ignored because of its affordances that improve students' cognitive engagement.